RESEARCH OF CONSTANT-LOAD CONTROL METHOD FOR ELECTROMAGNETIC RESONANT FATIGUE TEST SYSTEM - ZHOU Xun; YANG LiuQing; CHEN DaWei; YU CaiDong; HU Ming; CHEN WenHua (Jixie qiangdu)
In order to study the influence of testee’s crack growth on the vibration character of the system during the electromagnetic resonant fatigue testing,detailed FEA for modal and forced vibration with testees at different crack sizes were conducted. According to the results of the analysis,the dynamic relationships between the acceleration of the swing arm and the stress of the testee at different crack sizes are set up. The FEA results show that as the crack growing,the natural frequency and vibration character change accordingly,so it is necessary to change the exciting force to meet constant-load control request during the test. Finally,a method using the acceleration signal as the reference is proposed to achieve constant-load control.